Erik Satie's Vexations—An Exercise in Immobility - Dawson, Christopher (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2001)
Erik Satie's piano piece Vexations contains a Note de l’auteur in which the composer apparently instructs his interpreters to repeat the piece 840 times. Opinion among Satie's biographers is divided as to whether Satie intended a "full" performance of the piece. In this article I assess how a literary interpretation of the Note can throw light on Satie's intentions. My conclusion is that Vexations is not so much a performance piece as an exercise piece: a musical passage designed to pull his interpreters away from conventional Western notions of linear development and cumulative reception and towards his own non-developmental style of music, in preparation for a performance of a piece such as a Gymnopédie or a Gnossienne.